1996
DOI: 10.1113/jphysiol.1996.sp021814
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐evoked vasodilatation in human hairy skin: axon reflexes due to low‐level activity of nociceptive afferents.

Abstract: 1. Spreading vasodilatation of the axon reflex type was evoked by contact heat stimulation of the hairy skin in the human forearm (13X3 cm2 stimulus area) and was detected by laser Doppler flowmetry at 8, 19 and 30 mm distance.2. From a base temperature of 350, rapidly rising short heat stimuli (4°C s-1, 2 s plateau) elicited vasodilatation at an average threshold of 39 4 0C. For slowly rising sustained heat stimuli (64 s duration) the average threshold was 39-6 0C (n.s.). Laser Doppler flowmetry revealed a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 42 publications
8
112
1
1
Order By: Relevance
“…• C), vasoactive peptides are released in large quantities by nociceptive primary afferents, resulting in a significant increase in SkBF (Magerl & Treede, 1996). The distinctive SkBF patterns witnessed in the present study seem to support claims made by Minson et al (2002), who suggested that a smaller initial peak might be associated with a greater risk of local tissue damage in response to direct heat.…”
Section: Sympathetic Nervessupporting
confidence: 78%
“…• C), vasoactive peptides are released in large quantities by nociceptive primary afferents, resulting in a significant increase in SkBF (Magerl & Treede, 1996). The distinctive SkBF patterns witnessed in the present study seem to support claims made by Minson et al (2002), who suggested that a smaller initial peak might be associated with a greater risk of local tissue damage in response to direct heat.…”
Section: Sympathetic Nervessupporting
confidence: 78%
“…15 For example, excitation of C-fiber discharges need not be associated with pain sensation but can evoke a flare response. [11][12][13][14] The two may have different sensory/efferent pathways, and/or different sub-sets of nociceptors. 15,33 The difference in the flare and pain response to a heat-ramp stimulus among the normal and obese subjects may be indicative of such a dissociation and, in fact, would favor a concept that the organism attempts to elicit an early protective reaction (neurogenic vasodilatation) at a temperature (441C) just below that which will become injurious to tissue.…”
Section: Discussionmentioning
confidence: 99%
“…15,33 The difference in the flare and pain response to a heat-ramp stimulus among the normal and obese subjects may be indicative of such a dissociation and, in fact, would favor a concept that the organism attempts to elicit an early protective reaction (neurogenic vasodilatation) at a temperature (441C) just below that which will become injurious to tissue. 14 Flare can be suppressed or abolished by denervation, 21,42 local anesthetics, 12,21 capsaicin-desensitization, 22,34 disease (diabetes, post-herpetic neuralgia), 21,43 and aging. 32 Under circumstances of prolonged depression of small fiber function, tissue integrity can be substantially impaired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychophysical thresholds for heat pain range from 40 to 49 for stimulation at glabrous and hairy skin sites with probes of different sizes and with widely varying ramp rates and stimulus durations (Hamalainen et al 1982;LaMotte 1984;LaMotte et al 1983;Morin and Bushnell 1998;Pertovaara et al 1996;Strigo et al 2000;Wahren et al 1989;Yarnitsky and Ochoa 1991). Most of the mean threshold values cluster between 43 and 46°C (Craig and Bushnell 1994;Dyck et al 1993;Hardy et al 1952;Harju 2002;Magerl and Treede 1996;Nielsen and Arendt-Nielsen 1998;Taylor et al 1993;Tillman et al 1995;Torebjork et al 1984;Verdugo and Ochoa 1992). In experiment 2 of this study, eVAS ratings of 10 represent a conservative estimate of threshold pain.…”
Section: Discussionmentioning
confidence: 99%